An Empathetic Odyssey: A Film Review of Barbarian Invasion (2021) by Tan Chui Mui - Sheau-Shi Ngo (Wacana Seni Journal of Arts Discourse, 2024)
Barbarian Invasion is the latest feature film by Tan Chui Mui, a Malaysian independent film pioneer. The narrative has two parts. First, the film follows the character of Moon (played by Tan Chui Mui), a middle-aged actress forced to confront her midlife crisis while trying to return to her career. She brings her son to the beach to visit her old-time friend, Roger Woo (played by Pete Teo), who plans to make a kung fu film. Roger convinces Moon to take up the lead role in his upcoming film. Moon then began to receive kung fu training from Master Lo (played by James Lee). Second, Moon is acting as a muted illegal migrant woman who keeps fighting and running for her life.